2023
DOI: 10.1021/acs.inorgchem.3c01084
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking Cu(I)-Mediated Catalytic Pathways for Efficient ROS Generation by Incorporating an Oxazole-Based Histidine Surrogate into Cu(II)–ATCUN Complexes

Abstract: The catalytic redox activity of Cu(II) bound to the amino-terminal copper and nickel (ATCUN) binding motif (Xxx-Zzz-His, XZH) is stimulating the development of catalytic metallodrugs based on reactive oxygen species (ROS)-mediated biomolecule oxidation. However, low Cu(I) availability resulting from the strong Cu(II) binding affinity of the ATCUN motif is regarded as a limitation to efficient ROS generation. To address this, we replaced the imidazole moiety (pK a 7.0) of Gly−Gly− His−NH 2 (GGHa, a canonical AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The enhanced reactivity of both Cu­(II)-His 2 and Cu­(I)-His with H 2 O 2 likely results from the change in electronic properties of the central copper ion owing to the His-induced alteration in coordination geometry, including a higher shift in the reduction potential of the Cu­(II)/Cu­(I) couple. Several studies have reported more positive reduction potential values for the Cu­(II)/Cu­(I)-His containing compounds complexes ( E ° = 0.28–0.75 V ) than those in the absence of ligands ( E ° = 0.153 V). In addition to His, a similar shift in the Cu­(II) reduction potential has been observed upon the introduction of other ligands (e.g., chloride ion), which consequently enhanced the degradation of organic contaminants. , In a similar manner, His can also elevate the reduction potential of the Cu­(III)/Cu­(II) couple, thereby enhancing the oxidation power of Cu­(III) against recalcitrant organic pollutants, which warrants further study.…”
Section: Discussionmentioning
confidence: 98%
“…The enhanced reactivity of both Cu­(II)-His 2 and Cu­(I)-His with H 2 O 2 likely results from the change in electronic properties of the central copper ion owing to the His-induced alteration in coordination geometry, including a higher shift in the reduction potential of the Cu­(II)/Cu­(I) couple. Several studies have reported more positive reduction potential values for the Cu­(II)/Cu­(I)-His containing compounds complexes ( E ° = 0.28–0.75 V ) than those in the absence of ligands ( E ° = 0.153 V). In addition to His, a similar shift in the Cu­(II) reduction potential has been observed upon the introduction of other ligands (e.g., chloride ion), which consequently enhanced the degradation of organic contaminants. , In a similar manner, His can also elevate the reduction potential of the Cu­(III)/Cu­(II) couple, thereby enhancing the oxidation power of Cu­(III) against recalcitrant organic pollutants, which warrants further study.…”
Section: Discussionmentioning
confidence: 98%